The influence of seasonal and nonreciprocal evaporation duct on electromagnetic wave propagation in the Gulf of Aden - Bin Tian; Qianqian Liu; Jun Lu; Xiaoguang He; Guodong Zeng; Liu Teng (Results in Physics, 2020)
In this paper, the adaptability of ERA5 reanalysis data in the Gulf of Aden was validated by the data of shipborne sensors. Based on the reanalysis data, the seasonal distribution of nonreciprocal evaporation duct in the Gulf of Aden was obtained with PJ evaporation duct model. Using the empirical formula of the minimum trapping frequency, the seasonal variation of the minimum trapping frequency required for the formation of nonreciprocal propagation in the Gulf of Aden was analyzed. At the same time, the parabolic equation model was used to simulate the distribution of propagation loss of X-band electromagnetic radiation source along the typical path of the Gulf of Aden in four seasons. The results showed that the seasonal variation of evaporation duct in the Gulf of Aden is significant, and there is the highest EDH(evaporation duct height) in summer. In four seasons, the evaporation duct appears in the form of nonreciprocal distribution in the sea area. In autumn, the evaporation duct height inside and outside the bay is quite different. In summer, the minimum trapping frequency in the bay is the smallest. In autumn, the minimum trapping frequency outside the Gulf of Aden is higher than that in the bay and the difference between the two is great. In winter, the two are relatively close. In RD1(Route Direction 1), the propagation loss of electromagnetic wave in summer is lower than that in other three seasons, followed by winter. In spring and autumn, the electromagnetic wave propagation loss is larger than that in the other two seasons. In the different propagation directions of the same path, if the height distribution of the evaporation duct on the path is symmetric, the less the distance between the electromagnetic radiation source and the high-EDH distribution is, the lower the propagation loss of the electromagnetic wave is. The greater the height difference on the path is, the more obvious the propagation loss difference between the two propagation directions is. If the height difference on the path is small, the propagation loss difference in the two propagation directions is also small.